Inflation and relative price variability in the euro area: evidence from a panel threshold model - Juliane Scharff; Dieter Nautz (Deutsche Bundesbank, 2006)
In recent macroeconomic theory, relative price variability (RPV) generates the central distortions of inflation. This paper provides first evidence on the empirical relation between inflation and RPV in the euro area focusing on threshold effects of inflation. We find that expected inflation significantly increases RPV if inflation is either very low (below -1.38% p.a.) or very high (above 5.94% p.a.). In the intermediate regime, however, expected inflation has no distorting effects which supports price stability as an outcome of optimal monetary policy.
Keywords: C23; E31; 330; Inflation; Relative Price Variability; Panel Threshold Models; Inflation; Relativer Preis; Soziale Kosten; Schätzung; Deutschland